2020
DOI: 10.1111/jgs.16707
|View full text |Cite
|
Sign up to set email alerts
|

Harms and Benefits of Subcutaneous Hydration in Older Patients: Systematic Review and Meta‐Analysis

Abstract: OBJECTIVE To review all available original publications on the harms and benefits of subcutaneous (SC) hydration in older patients. DESIGN Systematic review and meta‐analysis. PARTICIPANTS All studies on SC hydration in older patients without restrictions on design or language. MEASUREMENTS The Medline, Embase, CINAHL, Cochrane Central Register of Controlled Trials, and Web of Science databases and trial registries were searched from inception to November 5, 2019, and two reviewers independently extracted the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
18
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 40 publications
5
18
0
3
Order By: Relevance
“…Recent literature has shown hypodermoclysis to be safe or equivalent to IV hydration in older adults, 9 or lower than in patients treated with IV infusions. 20 Similar to our study, one review found local oedema to be the most common toxicity. 20 Our study found 38.7% of patients to experience some form of ‘harm’ whilst on hypodermoclysis infusions, but it is important to note that our study included a broad range of adverse events as harms, ranging in type and severity.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Recent literature has shown hypodermoclysis to be safe or equivalent to IV hydration in older adults, 9 or lower than in patients treated with IV infusions. 20 Similar to our study, one review found local oedema to be the most common toxicity. 20 Our study found 38.7% of patients to experience some form of ‘harm’ whilst on hypodermoclysis infusions, but it is important to note that our study included a broad range of adverse events as harms, ranging in type and severity.…”
Section: Discussionsupporting
confidence: 89%
“…20 Similar to our study, one review found local oedema to be the most common toxicity. 20 Our study found 38.7% of patients to experience some form of 'harm' whilst on hypodermoclysis infusions, but it is important to note that our study included a broad range of adverse events as harms, ranging in type and severity. The collection of a broader range of harms is important, as these may impact the persons symptom burden and also the practical ability to deliver the infusion; and hence may influence the volume, rate or site of ongoing hypodermoclysis, or may influence cessation of therapy.…”
Section: Main Findingssupporting
confidence: 89%
See 1 more Smart Citation
“…The capacity to provide informed consent was evaluated by the patient’s physician and the study physician. This is in accordance with the ethical approval, which unfortunately excludes the delirious patient, in which SC hydration might be especially suitable [ 3 ]. Exclusion criteria were: fluid restriction, risk of acute deterioration of illness, and very short life expectancy.…”
Section: Methodsmentioning
confidence: 60%
“…Dehydration is a herald of death [ 1 , 2 ], and adequate fluid therapy is an important aspect of treating the older adult. Subcutaneous (SC) hydration is a safe and easy-to-apply method for parenteral fluid therapy recommended to treat mild dehydration and patients at risk of dehydration [ 3 5 ]. Previous studies have examined the absorption of SC hydration using radioisotopes to track fluid movement in younger adults [ 6 ] and healthy adults over 65 years [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%